PENGARUH STRUKTUR KEPEMILIKAN TERHADAP LUAS PENGUNGKAPAN TANGGUNG JAWAB SOSIAL (CORPORATE SOCIAL RESPONCIBILITY DISCLOSURE) PADA LAPORAN TAHUNAN (STUDI EMPIRIS PADA PERUSAHAAN PUBLIK YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Rahmawati, Hapsari Diah; Nazaruddin, Ietje (Universitas Muhammadiyah Yogyakarta, Indonesia, 2009)
This research is aims to examine the influence of structure ownership are considered by corporate social responsibility disclosure at annual report 2005-2007. The sample of this research is Indonesian Stock Exchange listed companies of the period 2005-2007, reporting complete annual report and reporting corporate social disclosure, and published at Indonesian Capital Market Directory (ICMD). The analysis method used is multiple regression. This result of the research shows that foreign ownership, institutional ownership, public ownership do not have effect to CSR disclosure, and Management Ownership have effect to CSR disclosure.